(untitled) (Scientific journal of the Fergana State University, 2025)
This article studies the influence of ecological factors on the development of silkworms and silk yield by evaluating different breeds of silkworms under the same conditions. In assessing the breeds of silkworms, factors such as viability, the yield of live silk from 1 g of worms, the percentage of quality silk, the weight of one quality silk cocoon, the silkiness of live silk, and the composition of the cocoons were taken into account. In the experiment, 1 g of silkworms was taken from the breeds and fed in four repetitions, with 250 mg taken in each repetition. It was observed that the sharp changes in atmospheric air, namely light, humidity, and temperature, directly affect the development of silkworms and silk yield. The impact of ecological factors on the development of silkworms and the variation of key indicators across different variants are discussed. Information about the works of scientists in this field is also provided. The relatively dry climate and low humidity conditions of the Fergana region are recommended for breeding the Istiqbol breed in the districts of Toshloq, Yozyovon, Oltiariq, and Qo’qon, while the Uzbekistan-6 and Zarafshon breeds are recommended for the districts of Fergana, So’x, Quva, and Rishton, which have higher humidity.